A rare case of Peutz Jeghers syndrome associated with gastric adenocarcinoma and multiple intestinal polyps - Saraf, Nidhi A.; Dave, Katha H.; Dalal, Archana D.; Suthar, Kalpit R.; Vaghela, Sagar J.; Patel, Chintan N.; Viajkhora, Muhammed A.; Patel, Kinju A.; Khatri, Dev H.; Damor, Sunita N. (International Surgery Journal, 2025)
Peutz-Jeghers syndrome (PJS) is a rare hereditary disease, inherited as autosomal dominant fashion (variable penetrance). It is characterized by hyperpigmentation over oral cavity and lips and gastrointestinal hamartomatous polyps. It has incidence rate between 1 in 50,000 and 1 in 200,000 people and prevalence of 1 in 100,000 people. Mucocutaneous pigmentations are most common clinical features in these patients. PJS patients have increased risk of gastrointestinal (more commonly) and extra intestinal malignancies. Incidence rate of gastric malignancy in PJS is around 5%. We presented a rare complication of PJS in terms of gastric adenocarcinoma. A 24 year old female presented with left lower abdominal pain on and off since one year. She had nausea, multiple episodes of gastric vomiting and obstipation since two days. On examination, hyperpigmented patches were present over both lips, had tachycardia. Abdomen was distended and tender. Abdominal ultrasound showed possibility of intussusception and CECT abdomen confirmed long segmental intussusception involving jejunal loops with lead point being polyp/hamartoma and presence of hamartoma/polyp in stomach and jejunum. Patient underwent Exploratory Laparotomy. Jejuno-jejunal intussusception was found. Intussusception could be reduced three big sessile polyps were found in it. Resection with jejuno-jejunal anastomosis was done. Postoperative course was uneventful. Upper GI scopy was done which showed multiple polyps in stomach, one large ulcerated polyp, biopsy from that polyp showed moderately differentiated adenocarcinoma. As the development of malignancies in PJS hamartomas is rare, periodic surveillance in patients and their family members is of utmost importance.